PENGELOLAAN STRES KERJA BIDAN DAN DAMPAKNYA TERHADAP KUALITAS PELAYANAN - Yeni Trisna Purba; Arthauly Gracia Sinaga; Putri Handayani Simbolon (Jurnal Minfo Polgan, 2023)
Midwives play a central role in the health system, particularly in maternal and child health services. However, high work demands, stressful work environments, and significant emotional burdens often make midwives vulnerable to occupational stress. This literature review examines the factors contributing to occupational stress in midwives, effective stress management strategies, and the impact of occupational stress on the quality of midwifery care and midwifery health. A thorough understanding of these issues is essential for developing interventions that support midwife well-being and ensure the provision of quality midwifery care.